2013
DOI: 10.1177/1010539513486921
|View full text |Cite
|
Sign up to set email alerts
|

Betel Quid Chewing Without Tobacco

Abstract: Betel quid without tobacco is an important factor influencing the incidences of oral cancer and precancer. This study systematically evaluated the associations between betel quid containing no tobacco and oral cancer and precancer, with implications for the prevention of oral cancer. We searched MEDLINE, ISI Web of Science, and EMBASE (to April 2011) and retrieved studies that investigated the relationship between chewing betel quid and oral cancer (or precancer). We performed a meta-analysis to summarize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The findings showed that the highest incidence of LOCC, overall and by sex, was found in countries in Oceania and Asia, countries with a history of high tobacco use in its various forms. Similar results have been reported previously, southeast Asian countries have a higher incidence of LOCC and a correlation with the geographical distribution of betel nut [ 28 ], which is considered a major risk factor for the development of potentially malignant lesions and oral cancers [ 29 ]. It is necessary, however, to undertake future studies to further delineate such phenomena.…”
Section: Discussionsupporting
confidence: 89%
“…The findings showed that the highest incidence of LOCC, overall and by sex, was found in countries in Oceania and Asia, countries with a history of high tobacco use in its various forms. Similar results have been reported previously, southeast Asian countries have a higher incidence of LOCC and a correlation with the geographical distribution of betel nut [ 28 ], which is considered a major risk factor for the development of potentially malignant lesions and oral cancers [ 29 ]. It is necessary, however, to undertake future studies to further delineate such phenomena.…”
Section: Discussionsupporting
confidence: 89%
“…Betel quid has been considered a carcinogen by the International Agency for Research on Cancer (IARC) for several years [ 27 ]. Previous results have shown that betel quid chewing has a significant negative effect on oral cancer and precancer [ 28 ]. Longer duration and higher frequency of betel quid chewing have been found to increase the risk of oral cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral cancer development is increased by a number of lifestyle choices including tobacco [8, 9] and alcohol use [10]. Particularly in Asia, betel quid (or paan) chewing (with or without tobacco [11, 12]) increases rates of oral squamous cell carcinoma (OSCC) and oral submucous fibrosis (OSMF) [1321]. Betel quid (typically consisting of betel leaf, areca nut, slaked lime, and possibly tobacco [22]) was identified as a contributer to increased oral cancer incidence as early as 1902 [23].…”
Section: Introductionmentioning
confidence: 99%